Thick slab punching with symmetry reductions. (9th February 2020) - Bocklenberg, Lennart; Mark, Peter
Abstract: The contribution presents a test series of four geometrically similar specimens of different size designed to investigate the punching behavior of thick reinforced concrete slabs. The thickness ranges from 300 to 650 mm and the slab radius varies between 1.12 and 2.45 m. For experimental execution, an innovative test method is employed and updated towards thick slabs. It uses the symmetry of specimens and reduces them corresponding to the symmetry grade to quarters. By applying this method, geometrical dimensions and associated test loads are reduced by 75%. The tests demonstrate on the one hand that the updated method is suitable for punching tests of thick specimens. And, on the other hand, the results indicate a less pronounced size effect for multilayered, highly reinforced slabs than predicted in theory.